Quality of life among mothers of preterm newborns in a Malaysian neonatal intensive care unit - Ong, Swee Leong; Soh, Kim Lam; Hussin, Emni Omar Daw; Japar, Salimah; Soh, Kim Geok; Vorasiha, Ponpun; Daud, Azlina (Belitung Raya Foundation, 2022)
Background: As Quality of Life (QoL) becomes progressively vital in health care services, its importance in mother and child health is of no exception too. Quality of life among mothers with a premature newborn is an issue that has led to growing concerns in the health care system. Yet, despite the knowledge about mother’s QoL being essential to family-centered planning on prematurity integrated healthcare, current evidence has been scant. Objective: To examine factors related to the QoL of mothers having preterm newborns hospitalized in the neonatal critical unit. Methods: A non-probability convenience survey was used in a public hospital in Malaysia, covering 180 mothers whose preterm newborns were hospitalized into level III Neonatal Intensive Care Unit (NICU) through the completion of a 26-questions survey of the World Health Organization Quality of Life (WHOQOL-BREF) and the 26-questions of Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU). The data were analyzed using descriptive statistics, bivariate analysis, and Pearson correlation coefficients. Result: The mean scores for mothers' quality of life were (M = 3.67, SD = 0.73) and maternal stress (M = 3.03, SD = 0.90) out of 5. A mother’s occupation was found to be the only factor associated with the quality of life among mothers who have preterm newborns admitted to the NICU. Furthermore, maternal role change was found to have a moderate negative relationship with the quality of life (r = 0.310, p = 0.05). Conclusion: The findings of this study revealed that the main factors contributing to the mother’s QoL during their preterm newborns’ NICU admission were role change-related stress. Thus, to maintain a better QoL among this group of mothers during this traumatic period, a special nursing intervention program must be implemented immediately, right after the preterm newborns’ admission, to relieve the mothers’ stress which has been proven to have a direct effect on the mothers’ QoL. The study results will alert healthcare providers, particularly neonatal nurses, on the need to support mothers psychologically in terms of role change. This is to ensure a better quality of life among mothers whose newborns were admitted to the NICU.